Critical review of the role of PPE in the prevention of risks related to agricultural pesticide use - Garrigou, A.; Laurent, C.; Berthet, A.; Colosio, C.; Jas, N.; Daubas-Letourneux, V.; Jackson Filho, J.-M.; Jouzel, J.-N.; Samuel, O.; Baldi, I.; Lebailly, P.; Galey, L.; et al. (Safety science, 2020)
•Cost, availability, and dangerous discomfort may make instructions to use PPE inapplicable.•The effectiveness of coveralls is not confirmed when PPE wearing practices are not controlled.•Nanotechnologies and low-dose effects are not considered in the assessment of PPE effectiveness.•The protective role attributed to PPE in the marketing authorisation of PPP should be questioned. Personal protection equipment (PPE) holds a privileged position in safety interventions in many countries, despite the fact that they should only be used as a last resort. This is even more paradoxical because many concerns have arisen as to their actual effectiveness under working conditions and their ability to provide the protection attributed to them by certain occupational safety strategies and marketing authorisation procedures. Are these concerns justified? This article is intended to provide an update on what we know of the issue based on a critical analysis of the literature to date. Analysis focuses on the assessment of the effectiveness of coveralls used to protect from plant protection products in OECD countries. All forms of assessment were retained: discussion of the observed effectiveness of PPE in relation to the underlying assumptions of marketing authorisation procedures, laboratory tests of equipment, practical field tests in which PPE-wearing practices were controlled and uncontrolled, analyses of the efficiency of preventive instructions based on wearing such coveralls. Findings show that recommending the use of PPE is key to the granting of marketing authorisation. Some dangerous products only get marketing authorisation because it is assumed that wearing PPE will considerably limit exposure. They would be banned if it were not for this assumption of protection. However the actual effectiveness of PPE in working conditions may be over-estimated. In addition many factors (cost, availability, thermic and mechanical discomfort) may make instructions to wear PPE inapplicable. Advising the use of PPE does not always mean effective protection.